Compressive strength of Super Soft wheat endosperm. (January 2020) - Delwiche, S.R.; Morris, C.F.; Kiszonas, A.M.
Abstract: Wheat endosperm texture (hardness) largely determines end-product suitability. Since its development 25 years ago, the single kernel classification system (SKCS, a mechanical instrument that measures, among other properties, the force imparted on a kernel during crushing) has been used in breeding programs to differentiate soft wheats from hard wheats. Nominally, these have a soft to hard SKCS hardness index (HI) range of 25–75 (dimensionless units). However, in recent years, breeders have developed extremely soft ('Super Soft') lines having SKCS HI < 0. Until now, these very low SKCS HIs have not been corroborated with traditional methodologies that characterize mechanical strength. Herein, we report on the relationships between SKCS HI and three compressive strength properties (maximum stress, Young's modulus, and work) in Super Soft wheat. With respective correlation coefficients of 0.76, 0.66, and 0.75, we have found that the relationships between SKCS HI and compressive strength agree with prior research involving ordinary soft and hard wheats. Graphical abstract: Image 1 Highlights: The physical strength properties of Super Soft wheat are a continuation of soft wheat. Engineering strength properties are positively correlated with SKCS hardness. Maximum stress and elastic modulus of elasticity are invariant of loading orientation.